Caracterização óptica e eletrônica de filmes semicondutores usando espectros de transmitância e refletância - Azevedo, Carlos Guilherme Gonçalves de [UNESP] (2015)
This work presents the end result of the developmet of a method for calculation of optical constants of semiconductor films based on measured transmitance (T) and reflectance (R), which allows the calculation of the spectral optical constants in the range of 0.5 eV to 5.0 eV, with possible extension to the middle and far infrared and the ultraviolet. The calculation method consists in the use of R spectra to improve and extend the determination of the values of the refractive index (n) and extinction coefficient (k). As a first approximation, the method is based on the T spectrum to calculate the n values in the spectral region of the interference fringes and the k values across the spectral range of T, as done in other methods. The improvement realized is related to the use of k values calculated initially from T spectrum, and aproximated n values - extrapolating the values obtained in the region of the interference fringes, to calculate refined n values using the R spectrum in the high absorption region. The method makes possible to determine the k values across the range in which the measured values T have good degree of accuracy. Another advantage observed in the present method is the possibility of refining the values of the optical constants using the R and T spectra alternately. The use of R enables a better fit to the n values, particularity the high absorption region (or anomalous dispersion region), while T spectra allow refined calculations of k, mainly above the bandgap, and the dispersion of the refractive index in low absorption. The calculations use the complete expressions for transmittance and reflectance, derived directly from Maxwell's equations. The expression used take into account the coherent multiple reflections in the films and incoherent in the substrate. The experimental work involved the transmittance measurements at a range of energy from 0.38 eV to 6.20 eV nm and reflectance measurement using integrating...